Characterisation of Antibiotic Resistant Pseudomonas Species in Environmental and Clinical Samples in Lafia, Nasarawa State (Lafia Journal of Scientific and Industrial Research, 2026)
Soil, water, and animals are reservoirs for resistance genes and multidrug resistant bacteria. The genus Pseudomonas is widely distributed in nature, with Pseudomonas aeruginosa being the most clinically significant. The aim of the study was to characterize antibiotic resistance in Pseudomonas species in environmental and clinical samples in Lafia, Nasarawa State. Water and soil (50 each) samples were collected five times per week, along with 50 urine samples. Samples with significant bacteriuria were analysed for positive isolates. The presence of virulence and antibiotic resistance genes on their DNA was confirmed with PCR analysis. Water samples had Pseudomonas counts ranging from 1.0x05 to 17.0x105 CFU/mL, and soil samples had highest count of 14.0x104 CFU/g. Pseudomonas species were 86.7% resistant to Augmentin and 75% resistant to Ceftazidime, while Ofloxacin had the lowest resistant isolates at 25%.  The multidrug resistance was 72.7% in the water isolates, 72.2% in urine, and 60.0% in soil isolates as the lowest. There was no significant association between sample source and MDR prevalence (p > 0.05). The resistance gene bla_VIM and virulence gene pvdM was each carried by 14 (82.4%) of the Pseudomonas sp. and six of them co-carried bla_VIM and bla_NDM genes. Pseudomonas mendocina isolate haboured neither virulence nor resistance genes. The findings calls for concern as the genes haboured by the Pseudomonas species encode resistance to carbapenems, the last resort antibiotics. Pseudomonas putida, a non-pathogenic isolates haboured bla_VIM and bla_NDM genes making them a reservoir for horizontal transfer to other isolates and bacteria in the environment.
Keywords: Pseudomonas; antibiotic resistance; multidrug resistance; environment